The economic theory of developing countries' rise : explaining the myth of rapid economic growth in China - Zhong, Yangsheng (University Press of America, 2010)
The Economic Theory of Developing Countries' Rise examines the great economic development achievements of China within such a short period of time, which have surprised the world and have also raised other developing countries' hopes for catching up with developed countries. Featuring traditional political economics and Chinese characteristics of socialism, this book is about the economics of developing countries' rise, based on the case of China and focuses on catching-up economic growth theory. Thus, the book is of interest to those who wish to know more about theories, practices, policies and causes of China's economic success. The original Chinese version has been a very influential and well-sold book written on economics in China, and has received numerous awards and accolades since it was first published in 1995. This English version is the translation of the sixth edition in Chinese, published in December 2005. Most recently, in August 2009, the Chinese book was selected and enrolled in the honorable book series - 100 Economist and their notable works impacting China's Economic Construction over the last 60 years.